PENGARUH PEMBERIAN PUPUK BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TOMAT (Lycopersicum esculentum Mill) - VERI DWI ARUM P.S; DWI SUSILO UTAMI; TEGUH SUPRIYADI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
Â Awareness of the consequences caused by the effects of agrochemical use, the attention of the world community begins to shift to environmentally have a conception agriculture.Then came the technology known as organic agriculture, which deals with organic and natural products, and overall does not use agrochemicals. Organic farming systems was expected to support and provide benefits in improving agriculture in the long term, improving environmental quality, and improving the quality of life of farmers. ThisResearch activity was carried out in Februari 23 2018 to June 12 2018 in Ngringin Village, Karangpandan District, Karanganyar Regency. This study aims to determine the response of growth and the results of tomato (Lycopersicum esculentum Mill) to bokashi dosage). The research method used a Complete Randomized Block Design (RCBD), consisting of one treatment factor and repeated three times with the level of P1 = 2 tons / ha, P2 = 4 tons / ha, P3 = 6 tons / ha, P4 = 8 tons / ha, P5 = 10 tons / ha, P6 = 12 tons / ha, P7 = 14 tons / ha, P8 = 16 tons / ha, and P9 = 18 tons / ha. This research is the initial process towards organic farming using bokashi fertilizer. The results of this study indicate: 1) Treatment of bokashi dosage of cow manure has a very significant effect on plant height (cm), number of leaves per plant (strands), weight of fresh stover (gram), weight of dry stover (gram), age of flowering (hst) , number of tomatoes per plant (fruit), weight of ripe tomatoes per plant (gram), weight of ripe tomatoes per plot (gram), volume of fruit (ml), weight of green tomatoes per plant (gram), and weight of green tomatoes per plot (gram ) 2) The highest ripe tomato weight is 18.52 tons / ha in P9 treatment (dosage of 18 tons / ha) and the lowest tomato weight is 8.88 tons / ha in P1 treatment (dosage of 2 tons / ha). 3) The highest weight of green tomatoes is 1.1 tons / ha in P9 treatment (dosage of 18 tons / ha) and the lowest weight of green tomatoes is 0.5 tons / ha in P1 treatment (dosage of 2 tons / ha).